Eco-Novel Food and Feed - De Sousa, Isabel Maria Nunes; Raymundo, Anabela; Torres, María Dolores (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Innovation is recognized as the key driver of economic growth. Trends in the food industry deal with a permanent need to develop new food products, adjusted to the consumer demands and, in the near future, to the scarcity of food resources. The concepts of sustainable food production and food products as health and wellness promoters, the use of alternative ingredients such as new protein sources, and the use of by-products in designing food or feed formulations according to bioeconomic principles, are current topics that act as driving forces for innovation. Currently, food and feed product development methodologies are generally based on chemical and nutritional properties, complemented with a sensory validation carried out in the final stages of the development process. In the creative process, the food macromolecules are the major players for the creation of relevant food structures such as foams, emulsions, and gels. The development of gluten-free or vegetarian products using alternative proteins and polysaccharides, the use of food industry by-products as sources of these structuring biopolymers, and the structural implications of adding protein and/or fiber-rich healthy ingredients are some of the challenges in creating novel food and feed products. Finally, the consumer attitude towards new food products is a relevant issue for the success of the novelties, and should be considered for close-to-market novel products.